Multi-Level, Multi-Component Intervention Improves Dietary Intake in Native American Adults - Redmond, Leslie (Curr Dev Nutr, 2021)
OBJECTIVES: To assess impact of a multi-level, multi-component (MLMC) intervention on dietary intake in Native American adults. METHODS: A MLMC obesity intervention ([blinded for review]) was implemented among Native American adults in six rural tribal communities in the US Southwest and Midwest. [Blinded for review] included institutional level components, demonstrations, and distribution of educational media/materials in food stores, worksites, and schools. Communities were randomized to intervention (Group 1; n = 3) or control (Group 2; n = 3). Data collection surveys included a semi-quantitative Block food frequency questionnaire and an Adult Impact Questionnaire for demographics and anthropometrics. This analysis assessed change in daily energy and macronutrient intake from baseline to follow-up, daily intake of types of dietary fat, and daily servings of food groups as defined by the 2015–2020 Dietary Guidelines for Americans using multilevel mixed-effects linear regression with clustering at the community level. All models were adjusted for age, gender, education, Material Style of Life score (proxy for socio-economic status), smoking, and baseline dependent variable of interest. RESULTS: 492 participants completed both baseline and post-intervention surveys: 31 were excluded due to reports of daily caloric intake outside of established cut-offs (<500 kcal or >7000 kcal per day), and 15 were excluded due to incomplete data, for a total n = 446 for this analysis. The between group effect was significant for change in energy intake (−188.21 kcal; P = 0.050), total grams of carbohydrate (−22.48 g; P = 0.047), total grams of fat (−8.82 g; P = 0.044), and total grams of saturated fat (−3.19 g; P = 0.031), with greater decreases observed in Group 1. Change in total grams of sugar trended towards significance (−12.06 g; P = 0.057); similarly, greater decreases were observed in Group 1. Change in daily servings of fats and sweets was also significantly different between groups (−0.39 servings; P = 0.036), with greater decreases observed in Group 1. CONCLUSIONS: MLMC interventions can significantly impact dietary intake among rural Native American adults. This is especially important given the high risk of obesity and other diet-related chronic diseases among Native American adults. FUNDING SOURCES: National Heart, Lung, and Blood Institute